Enhanced 2 μm emission behavior and energy transfer in Ho3+/Yb3+ co-doped bismuth-tellurite fiber-core glasses by CeO2. (July 2023) - Song, Chunlai; Cong, Yuxuan; Zhou, Dechun; Cao, Jilong; Han, Kexuan; Zhang, Chi; Bai, Yuerong; Wu, Yuxiao
Highlights: The 2 μm band emission properties of bismuth-tellurite glass can be enhanced by energy transfer possess modified. The topology structure units of the bismuth-tellurite glass can be investigated comprehensively by using Gaussian fitting. The emission cross-section of Ho 3+ : 5 I7  →  5 I8 in TBZHYC2 glass has been enhanced by about 10 % compared with TBZ glass (from 1.01 × 10 −20  cm 2 to 1.11 × 10 −20  cm 2 ) when the concentration of CeO2 is 0.3 mol%. Abstract: Ho 3+ /Yb 3+ co-doped and Ho 3+ /Yb 3+ /Ce 3+ tri-doped 85TeO2 –5Bi2 O3 –10ZnO glasses were synthesized by the melt-quenching method. The structural and spectral properties were investigated comprehensively according to Raman, absorption, and fluorescence spectra. By evaluating the energy transfer process, the 2 μm emission behavior has been enhanced effectively with the introduction of a glass network modifier (CeO2 ), which can be ascribed to the population of Ho 3+ : 5 I7 accelerated by cross-relaxation (CR) between Ho 3+ and Ce 3+ . A large emission cross-section (1.11 × 10 −20  cm 2 ) and gain coefficient (2.12 cm −1 ) have been obtained of Ho 3+ at around 2 μm band in TBZHYC2 glass, where a significant advancement has been achieved compared with the glass fiber core without CeO2 . Moreover, the energy transfer mechanisms between Ho 3+ /Yb 3+ and Ho 3+ /Ce 3+ were quantitatively analyzed based on a spectral overlap method. As mentioned above, Ho 3+ /Yb 3+ /Ce 3+ tri-doped bismuth-tellurite glasses are potentially competitive and applicable in the field of 2 μm band infrared fiber lasers as a kind of novel laser glass.